2015
DOI: 10.1371/journal.pone.0137930
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Behavioral and Neural Correlates of Executive Functioning in Musicians and Non-Musicians

Abstract: There is an error in Table 1. The Mean ± SD of 'Duration of musical training (years)' for 'Adult Musicians' is incorrect. Please see the correct Table 1 here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Furthermore, although musicians can have a stronger emotional reaction to musical sadness, it can also be coupled with more cognitive processing of such sadness in music (Park et al, 2014). Overall, music training may possibly foster better cognitive control/executive functions in musicians (Okada & Slevc, 2018; Pallesen et al, 2010; Zuk et al, 2015). In turn, this may afford some emotional protection as cognitive control/executive functions are supposed to foster successful emotion regulation (Ochsner & Gross, 2005; Schmeichel & Tang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although musicians can have a stronger emotional reaction to musical sadness, it can also be coupled with more cognitive processing of such sadness in music (Park et al, 2014). Overall, music training may possibly foster better cognitive control/executive functions in musicians (Okada & Slevc, 2018; Pallesen et al, 2010; Zuk et al, 2015). In turn, this may afford some emotional protection as cognitive control/executive functions are supposed to foster successful emotion regulation (Ochsner & Gross, 2005; Schmeichel & Tang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are given by Roden et al (2014), who evaluated working memory in 7- to 8-year-old children following an 18-month music programme and found that the students showed an increase in auditory information processing. Musical training favours the development of working memory from early childhood because music learning involves cognitive functions of coding, storage and retrieval associated with memory (Zuk et al, 2015). For example, phonological memory has been found to be a predictor of pronunciation ability along with perception and auditory discrimination in children who begin learning music at an early age (Hu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Evidências a favor da flexibilidade cognitiva associada ao contexto musical têm sido sido produzidas por estudos que apontam que crianças submetidas à experiência musical apresentaram maiores taxas de oxigenação cerebral (BOLD) em regiões do cérebro associadas ao funcionamento executivo (e.g. córtex pré-frontal ventrolateral; área motora suplementar) (Nachev, Kennard & Husain, 2008;Nee et al, 2013;Zuk et al, 2014) em respostas a testes de alternância, comumente utilizados para verificação da flexibilidade cognitiva, quando comparadas a crianças que não possuem treinamento musical.…”
Section: Referênciasunclassified